2016
DOI: 10.7717/peerj.2727
|View full text |Cite
|
Sign up to set email alerts
|

Harmine stimulates proliferation of human neural progenitors

Abstract: Harmine is the β-carboline alkaloid with the highest concentration in the psychotropic plant decoction Ayahuasca. In rodents, classical antidepressants reverse the symptoms of depression by stimulating neuronal proliferation. It has been shown that Ayahuasca presents antidepressant effects in patients with depressive disorder. In the present study, we investigated the effects of harmine in cell cultures containing human neural progenitor cells (hNPCs, 97% nestin-positive) derived from pluripotent stem cells. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 42 publications
4
50
0
1
Order By: Relevance
“…Our results for the effect of harmine on proliferation are in line with a previous study showing harmine-induced increase in mitosis in cultured chick embryo cells 32 , and in human neural progenitor cells 33 . To our knowledge, the effects of harmaline and THH on neurogenesis have not been studied before.…”
Section: Discussionsupporting
confidence: 92%
“…Our results for the effect of harmine on proliferation are in line with a previous study showing harmine-induced increase in mitosis in cultured chick embryo cells 32 , and in human neural progenitor cells 33 . To our knowledge, the effects of harmaline and THH on neurogenesis have not been studied before.…”
Section: Discussionsupporting
confidence: 92%
“…Recent reports suggest the possible role of harmine in neurogenesis 69 . Furthermore, it is known that DMT act as an agonist at 5-HT 1A receptors 8,70 .…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…The fact is that we still do not know what DMT is doing in our bodies, so this is a very interesting topic to further investigate 9,10 . Moreover, preclinical studies suggest that DMT and the β-carbolines have not only antidepressive, anxiolytic, and antiaddictive proprieties 39,40 , but also neuroprotective and neurotrophic potentials 69,[77][78][79] . For instance, a recent neuropsychological study in ayahuasca user suggested that ayahuasca may indeed improve cognition and have "nootropic" effect 80 .…”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…To induce hESCs towards neural differentiation, we adapted Baharvand and coworkers' protocol (Baharvand et al 2007;Dakic et al 2016). Briefly, 70%…”
Section: Human Neural Progenitor Cellsmentioning
confidence: 99%
“…hNPCs were expanded for no more than 5 passages. Basic characterization of this culture was published in Dakic et al, 2016.…”
Section: Human Neural Progenitor Cellsmentioning
confidence: 99%